Gateway to Corregidor a historical revitalization and waterfront development - Almanzor, Mark; Dejos, Verna; Sicam, Olivia; Silvestre, Danilo A.; Santaromana, Francis (Quezon City College of Architecture, University of the Philippines Diliman, 1999)
Our lives change like continuously like the changing of the tides. Life attuned with the movement of water, imitates and is itself moved by it through the passage of time. Water is a large contributor to the making of history as it gives life, erodes rock and leads man to endless travel and exploration. Though strongly connected, seldom is the experience captured at one given moment. Man's love of sea and river gives him recreation and a way of life. History, on the other hand, is sought in museums and old preserved surroundings to give him a sense of his roots. These two vital elements can be consummated at the historical waterfront.
Corregidor exemplifies both water and history as its strategic location in the mouth of Manila Bay makes it a natural magnet to the ancient sea traveler.
The sea plays an important role in the craggy Corregidor landscape, shaping its cliffs through centuries of time and leading the wayfarer to its pristine beaches. Historically, it acted as a gateway to galleons that plied their route into the archipelago. The island also made its name during World War II when it became known as the great bastion of defense built by the American Military.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Waterfronts -- Corregidor